Millimeter wave 5G wearable antennas - Lim, Xuan Min (Nanyang Technological University, 2023)
In this report, a Final Year student’s Coplanar Waveguide-fed Triple-band Liquid Crystal Polymer wearable antenna is presented. It has overall dimensions of 43mm x 20mm x 0.2mm. This antenna operates Wireless Local Area Network (WLAN), Worldwide Interoperability for Microwave Access (WiMAX), and 5G sub-6 GHz frequency band. The proposed antenna uses CPW feeding, and 2 L-shaped stubs integrated into the rectangular radiation patch. The antenna is printed on 0.2 mm thick LCP substrate. The simulation shows reasonable gain and radiation characteristics.